Libertarian model of cultural conservatism - A. D. Parfenov (Омский научный вестник: Серия "Общество. История. Современность")
The article presents an analysis of theories and approaches to substantiate the synthesis of libertarian political philosophy and cultural conservatism. In a historical perspective, the genesis of the main concepts and methods underlying the theories under study is shown. Emphasis is placed on the arguments and arguments presented by the supporters of this political and philosophical model. The main purpose of the article is to identify the features of the substantiation of the libertarian-conservative synthesis, as well as the main advantages and disadvantages of the proposed arguments.